Trade Union Personality Girl contest, Newcastle, c1960
1961 1960-2000 "Trade Union Personality Girl contest, Newcastle, c1960" [T0418.jpg], c1960 In the early 1960s, Personality Girl Contests were a popular method of recruiting young women into unions. The London Trades Council organised an annual event.